Yemen : Exchange Rate Policy in the Face of Dwindling Oil Exports - Schneider, Todd (IMF Working Papers; Working Paper ;, 2007)
This paper investigates the likely implications of declining oil production on Yemen's equilibrium exchange rate, and discusses policy options to ensure a smooth transition to a nonoil economy. The empirical results suggest that, as oil production and foreign exchange earnings fall, the Yemeni rial will have to adjust downward in real effective terms to keep pace with the equilibrium exchange rate. In light of strong pass-through from exchange rate depreciation to domestic inflation, this could entail a substantial depreciation in nominal terms. Given the nature of the adjustment, a floating exchange rate regime appears to be the best option, if supported by appropriate macroeconomic policies. However, given public fixation on a exchange rate stability, a softly managed float would be a better option for Yemen whereby the central bank may have to lead the market toward the equilibrium exchange rate.